The Political plurality: A Study of the Concept and Mechanisms - Afdo Ali, Wageeh (Journal of Duhok University, 2019)
Political plurality considers as a cornerstone of building of a modern civil state which seeks to achieve social homogeneity through the recognition of the society in plurality and diversity and allow them to express their characteristics freely without coercion. Therefore, the plurality and diversity should be adopted and considered in the Iraqi society that has been facing problems in dealing with such issues. The fragility and vulnerability of current democracy in Iraq mainly because the absence of political plurality in Iraq in the last decades and because the successive totalitarian regimes which have governed the country did not allow the freedom of opinion and the formation of political parties.